Measurement invariance of a neuropsychological battery across urban and rural older adults in Costa Rica - Valdivieso Mora, Esmeralda (2022)
This study evaluated the measurement invariance of a neuropsychological battery across rural and urban older adults from Costa Rica. Rural and urban older adults (N = 295) from the Epidemiology and Development of Alzheimer’s Disease (EDAD) study in Costa Rica were assessed. The baseline factor model for the EDAD neuropsychological measures was identified with nine neuropsychological measures and three cognitive constructs: Verbal Memory, Spatial Reasoning, and Cognitive Flexibility. Measurement and structural invariance were established, and, then, group comparisons of the latent cognitive factors were conducted to explore regional disparities. The findings showed that most of the neuropsychological tests in EDAD can be directly compared across the groups, allowing for cognitive constructs comparisons. The rural sample showed a disadvantage in the Spatial Reasoning and Cognitive Flexibility abilities. When age and education were included in the models, differences between the regions disappeared. Having more years of education was associated with higher cognitive abilities, with a larger effect for the rural group. Norms for Costa Rican older adults should consider age and education adjustments. This study contributes to the growing area of measurement invariance in neuropsychological assessment as it highlights the importance of examining the comparability of assessment measures across different cultural groups.